2006
DOI: 10.1002/hyp.6289
|View full text |Cite
|
Sign up to set email alerts
|

Studies on groundwater recharge characteristics at a reclaimed land site with an equatorial climate using time‐series and spectral analyses

Abstract: Groundwater recharge studies are essential for investigating the feasibility of using the reclaimed lands in Singapore for subsurface storage and recovery of water. Through time-series and spectral analyses, net recharge percentages and stressfiltering characteristics at the reclaimed land were found to depend strongly on the stress transfer velocity, which was a combined function of rainfall pattern and vadose zone thickness. Based on stress transfer velocity, a theory was established to provide logical expla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…The theory of residence time t R established in the present study provides physical proof for the theory of stress transfer velocity (Tan et al, 2007) developed from time-series and spectral analyses. This previous study observed that net recharge percentages and stress filtering characteristics at the Changi Reclaimed Land depend strongly on the stress transfer velocity, which was a combined function of rainfall pattern and vadose zone thickness.…”
Section: Physical Explanations To Rainfall-recharge Relationshipsupporting
confidence: 57%
“…The theory of residence time t R established in the present study provides physical proof for the theory of stress transfer velocity (Tan et al, 2007) developed from time-series and spectral analyses. This previous study observed that net recharge percentages and stress filtering characteristics at the Changi Reclaimed Land depend strongly on the stress transfer velocity, which was a combined function of rainfall pattern and vadose zone thickness.…”
Section: Physical Explanations To Rainfall-recharge Relationshipsupporting
confidence: 57%
“…Nevertheless, rainfall recharge characteristics at unconfined sandy aquifers were found to be significantly different between isolated rainfall events and rainfall clusters. Compared to isolated rainfall events, rainwater from intense rainfall clusters was found to propagate more rapidly from the soil surface to the water table, leading to a significantly higher groundwater recharge percentage at the unconfined sandy aquifer (Tan et al, 2007c). In order to apply the developed equations on rainfall clusters, additional guidelines were established to integrate the effects of rainfall clusters into the estimation.…”
Section: Recharge Estimation Methodsmentioning
confidence: 99%
“…To obtain the rainfall-induced water level fluctuations, the time series of daily water-level fluctuations were filtered using low pass filter, as the wave component contributed by rainfall recharge was found to have a frequency band between 0 and 0Ð0938 cycle/day (Tan et al, 2007c). On the basis of the Equation (8), the monthly net groundwater recharge percentages R(%) at the study site were computed using:…”
Section: Other Estimation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Water from these drains is routed directly to the Singapore Strait. This study is one of several carried out at this site exploring the feasibility of using the area for groundwater storage and in situ treatment (Chua et al, 2007;Ngonidzashe, 2004;Tan et al, 2007c…”
Section: Study Sitementioning
confidence: 99%